PENGARUH PENGGUNAAN HANDPHONE TERHADAP PRESTASI BELAJAR SISWA SMA PLUS AL-ASIYAH CIBINONG PADA KELAS X - Maulana Zuama; Moch Sahidin; Noor Hidayat (Jurnal Riset dan Transformasi Pendidikan, 2026)
This research is a field research, namely the researcher conducted field research to the location to obtain and collect data. This research is descriptive qualitative, where the data collected is in the form of written or spoken words from people and observable behavior at SMA Plus Al-Asiyah Cibinong. Location and object of research SMA Plus Al-Asiyah, Jl Raya Jakarta-Bogor no.747 Rt.002 / Rw 006 Pabuaran, Cibinong District, Bogor Regency, West Java 16916. With the target object of 28 students of Class X / 1, 26 females and 2 males. The instruments used in this study were Observation and Interviews. The data collection methods used were Observation and Interviews. The analysis technique used in solving the main problem is a qualitative descriptive analysis technique. The results of the study showed that the use of mobile phones in schools greatly disrupts the teaching and learning process and has a negative impact on student achievement, although there are a small number of them who still get high achievements because they do not misuse mobile phones and only use them to access information related to lessons. The results of the study provide suggestions as a consideration, namely for schools, to be able to implement rules regarding the prohibition of the use of mobile phones at school because it can disrupt the seriousness and concentration of students in paying attention to lessons and of course this is closely related to the decline and increase in student learning achievement.